Determinants of bank profitability in developed and developing countries before and during the crisis - Latisevs, Jevgenijs (2011)
This paper investigates the profitability of commercial banks in developed and developing countries over the period from 2002 to 2010. The United States, the United Kingdom, Germany and Japan are used in the analysis as developed countries and Brazil, Russia, India and China are taken as an example of developing countries. To evaluate the impact of the recent global financial crisis, the sample data was split into two periods: the period from 2002 to 2006, the pre-crisis period; and the period from 2007 to 2010, the crisis period. Profitability determinants used in the analysis include bank-specific, industry-specific and macroeconomic factors. Consideration of the pre-crisis and the crisis periods contributed to better understanding of what determines the profitability of commercial banks, and more importantly how they were affected by the crisis. The empirical findings provide some evidence that the recent global financial crisis had a significant impact on the profitability of banking industry in most developed and developing countries. Furthermore, findings reveal that predominantly macroeconomic and industry-specific determinants have relatively small impact on the overall explanatory power of regression models for both developed and developing countries, but individually they appear to significantly affect bank profitability. Most significant determinants of bank profitability in developed countries appear to be liquidity risk, bank size, bank capitalisation and level of financial market development, whereas in developing countries most significant determinants are liquidity risk, credit risk, efficiency of operating expenses and growth of gross domestic product.